Case reportBlue rubber bleb naevus syndrome – case report - Samochocki, Zbigniew; Dejewska, Jowita; Bogusławska-Walecka, Romana; Wojtuń, Stanisław; Koktysz, Robert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Blue rubber bleb naevus syndrome (BRBNS) is an uncommon and rare disorder characterised by multiple venous malformations of the skin and many internal organs. Angiomas involving internal organs may be the cause of bleeding resulting in profound anaemia, acute haemorrhage, intussusception or even death. The skin lesions are usually multiple, disseminated, generally small, bluish-purple, soft vascular tumours with rubber-like texture (which explains the syndrome’s full name). The most common extracutaneous localization of vascular malformations is the gastrointestinal tract, and particularly the small intestine. We report a case of BRBNS in a 52-year old woman, with disseminated skin changes which developed over approximately two years, predominating on the upper trunk and in the oral cavity. The histological findings were characteristic for the syndrome. No pathological findings were present on examination of internal organs.